Syarat Pendirian dan Tanggung Jawab Pemegang Saham Perseroan Perorangan - Rongiyati, Sulasi (Pusat Analisis Keparlemenan Badan Keahlian Setjen DPR RI, 2023)
As a strategic component of the national economy, micro, small, and medium enterprises (MSMEs) have made significant contributions to employment and the gross domestic product. Paradoxically, MSMEs, particularly micro and small enterprises (MSEs), continue to encounter challenges in their business operations. With the enactment of the Law on Job Creation, subsequently replaced by the Government Regulation in Lieu of Law (Perppu) on Job Creation, the government introduced policies aimed at facilitating business activities for entrepreneurs, including MSEs. The establishment of individual companies represents a significant policy breakthrough for MSEs. This research employs a normative juridical approach with qualitative analysis. The research examines the regulatory requirements and mechanisms governing the establishment of individual companies as part of the ease-of-doing-business provisions outlined in the Perppu on Job Creation. Additionally, it explores the responsibilities of shareholders in relation to individual companies. The analysis reveals that the regulations pertaining to individual companies prescribe simplified requirements for the establishment, such as individual registration, electronic registration, exemption from notary deeds, flexibility in authorized capital arrangements, and the obligation to convert the status of individual companies if it fails to meet the minimum wage criteria. Shareholders’ responsibilities are limited to their invested capital, and they are not personally liable for the company’s engagements or losses exceeding their share ownership. This research recommends that the government enhance the regulation of individual companies, particularly regarding shareholder responsibilities. AbstrakUsaha Mikro, Kecil, dan Menengah (UMKM) sebagai bagian strategis perekonomian Nasional telah memberikan kontribusi signifikan terhadap penyerapan tenaga kerja dan Produk Domestic Bruto. Ironisnya UMKM, khususnya Usaha Mikro Kecil (UMK) masih menghadapi permasalahan dalam menjalankan usahanya. Melalui pembentukan UU tentang Cipta Kerja yang kemudian diganti dengan Perpu tentang Cipta Kerja, pemerintah membuat kebijakan kemudahan berusaha bagi pelaku usaha, termasuk UMK. Pendirian Persero Perorangan menjadi terobosan kebijakan khusus bagi UMK. Penelitian ini merupakan penelitian yuridis normatif yang dianalisis secara kualitatif. Tulisan ini mengkaji pengaturan persyaratan dan mekanisme pendirian Perseroan Perorangan sebagai bagian dari kemudahan berusaha yang diatur dalam Perpu Cipta Kerja; serta tanggung jawab pemegang saham terhadap Perseroan Perorangan. Hasil analisis menggambarkan regulasi terkait Perseroan Perorangan mengatur persyaratan yang lebih mudah dalam pendirian, antara lain pendirian dilakukan perorangan, pendaftaran secara elektronik, tidak memerlukan akta notaris, penyesuaian pengaturan modal dasar, dan kewajiban mengubah status Perseroan Perorangan apabila sudah tidak memenuhi kriteria UMK. Tanggung jawab pemegang saham terbatas pada modal dan tidak memiliki tanggung jawab secara pribadi atas perikatan yang dibuat oleh perseroan serta tidak bertanggung jawab terhadap kerugian melebihi saham yang dimiliki. Tulisan ini merekomendasikan kepada pemerintah penyempurnaan regulasi Perseroan Perorangan, khususnya pengaturan tanggung jawab pemegang saham Perseroan Perorangan.